Industrial Growth, Housing Gaps: Assessing Flat Needs for Workers (Case of Pringapus, Indonesia) - Suanti, Elvana Akar Yoga Elsisi; Amrullah, Karim (Universitas Negeri Semarang, 2025)
This study aims to analyze the needs and planning of flats for workers in the industrial area of ​​Pringapus District, Semarang Regency. Along with the development of the industrial sector in this area, the demand for decent housing for workers is increasing, but has not been balanced by the provision of flats that are in accordance with their needs. Based on demographic data and labor density in the area, this study will identify the conditions of housing needs as well as technical, social, and environmental aspects that need to be considered in planning decent and sustainable flats. The main focus of this study is how an effective flat planning model can be applied, taking into account the economic limitations of workers and the need to create a safe and comfortable residential environment. The method used in this study is normative legal research, which includes an analysis of laws and regulations, government policies, and relevant literature on flat planning for workers in industrial areas. The results of this study are expected to provide recommendations for better planning and construction of flats in the Pringapus industrial area, as well as support government policies in providing affordable and decent housing for workers.